EFEKTIVITAS MEDIA EXPLOSION MAGIC BOX UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN FIKIH DI MA AL-IHSAN KALIKEJAMBON - Ella Nur Indah Sari; Umi Chaidaroh; Didin Sirojudin (JoEMS (Journal of Education and Management Studies), 2020)
This study aims to determine the effectiveness of the explosion magic box learning media in fiqh class XI subjects at MA Al-Ihsan Kalikejambon. The population in this study were all students of class XI, amounting to 47 students. The sample used was 29 students from class XI IIS and 18 students from class MIPA. The method used is quantitative research methods and types of field research. Methods of data collection using a questionnaire, observation methods, methods of learning outcomes test (pre-test and post test) and documentation. Media Explosion Magic Box represents an explosion, in the shape of a box, when opened it will form a grid of boxes and create text or images according to the theme. The results showed that there was a significant difference in the mean score of student learning outcomes in the pre-test and post-test after being taught using Explosion Magic Box media. This can be seen in the results of hypothesis testing through the Paired Sample t-test. The significance value (Sig. (2tailed) is lower than the significance level of 0.05 (0.000 <0.05), which means that the research data is considered to have a significant difference in the mean pre-test and post-test. , this research hypothesis is accepted. In this case, it can be concluded that the Explosion Magic Box Media is effective for improving student learning outcomes in Islamic Civilization History subjects at MA Al-Ihsan Kalikejambon Tembelang Jombang.